The Benefits and Challenges of Video Calling for Emergency Situations - Neustaedter, Carman; Jones, Brennan; O'Hara, Kenton; Sellen, Abigail (CHI 2018, Montreal, QC, Canada, 2018)
In the coming years, emergency calling services in North America will begin to incorporate new modalities for reporting emergencies, including video-based calling. The challenge is that we know little of how video calling systems should be designed and what benefits or challenges video calling might bring. We conducted observations and contextual interviews within three emergency response call centers to investigate these points. We focused on the work practices of call takers and dispatchers. Results show that video calls could provide valuable contextual information about a situation and help to overcome call taker challenges with information ambiguity, location, deceit, and communication issues. Yet video calls have the potential to introduce issues around control, information overload, and privacy if systems are not designed well. These results point to the need to think about emergency video calling along a continuum of visual modalities ranging from audio calls accompanied with images or video clips to one-way video streams to two-way video streams where camera control and camera work need to be carefully designed.